Seleksi Toleransi Kekeringan In Vitro terhadap Enam Belas Aksesi Tanaman Terung (Solanum melongena L. ) dengan Polietilena Glikol (PEG) - Erna Sinaga; Megayani Sri Rahayu; Awang Maharijaya (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2015)
ABSTRACTThe objectives of this study were to study the effect of several concentrations of polyethylene glycol (PEG) on the in vitro growth of eggplant, to find the appropriate PEG concentration for in vitro selection to drought tolerance of eggplant and the drought tolerant eggplant accessions. The experiment was conducted at the Laboratory of Tissue Culture, Department of Agronomy and Horticulture, Bogor Agricultural University. The experiment was arranged in a completely randomized design with two factor. The first factor was concentration of PEG (0, 5, 10, and 15%) while the second factor was eggplant accessions (Kania F1, 001, 007, 013, 016, 030, 034, 035, 055, 057, 069, 071, 072, 078, 085, and 090). The results showed that the addition of PEG to in vitro media significantly affected the survival percentage, the percentage of callus, developed the bud and the number of leaves of eggplant. Addition of PEG 10 and 15% in media can be used as the drought tolerance selective agent of eggplant in vitro. Kania F1, 001, 007, 016, 034, 035, 055, 057, 069, 071, 072, 078, 085, and 090 were eggplant accessions which might be tolerant to drought.Keywords: in vitro selection, solanaceae, tissue culture, tolerant, drought ABSTRAKPenelitian ini bertujuan untuk mempelajari pengaruh beberapa konsentrasi polietilena glikol (PEG) terhadap pertumbuhan tanaman terung in vitro, mendapatkan konsentrasi PEG yang dapat digunakan untuk seleksi tanaman terung secara in vitro dan nomor terung toleran terhadap cekamankekeringan. Penelitian ini dilaksanakan di laboratorium Kultur Jaringan, Departemen Agronomi dan Hortikultura, Institut Pertanian Bogor. Penelitian ini disusun dalam rancangan acak lengkap dua faktor. Faktor pertama adalah konsentrasi PEG terdiri atas 0, 5, 10, dan 15%. Faktor kedua adalah nomor terung terdiri atas enam belas nomor (Kania F1, 001, 007, 013, 016, 030, 034, 035, 055, 057, 069, 071, 072, 078, 085, dan 090). Hasil penelitian menunjukkan bahwa penambahan PEG pada media in vitro memberikan pengaruh nyata dan sangat nyata terhadap persentase hidup eksplan, persentase eksplan berkalus, pertambahan tinggi tunas, dan jumlah daun tanaman terung. Media PEG 10 dan 15% merupakan media yang dapat digunakan untuk seleksi kekeringan tanaman terung in vitro. Nomor terung Kania F1, 001, 007, 016, 034, 035, 055, 057, 069, 071, 072, 078, 085, dan 090 merupakan nomor-nomor terung yang toleran terhadap cekaman kekeringan.Kata kunci: kultur jaringan, seleksi in vitro, solanaceae, toleran kekeringan